Knowledge Acquisition, Organization, and Use in Biology
245 p.
Keywords: Biology education, like science education in general, is in the midst of a revolution that is worldwide in scope. The changes in the ways science education researchers think about learning and understanding represent a major paradigm shift. In this book, international leaders in the field of biology education research give summaries of problems and solutions in biology learning and teaching at various grade levels. Based on a NATO workshop in the Special Programme on Advanced Educational Technology, it provides practical information for teachers, especially in using new interactive, constructivist teaching methods. For science education researchers, it offers a concise summary of a number of research issues in biology education.